The effect of type of cementing material and veneer thickness on the depth of cure of porcelain veneer restorations - Limjap, Ysabella Kristel M.
Introduction: The researchers investigated the depth of cure of two possible cementing medium for porcelain veneer restorations: the standard veneer resin cement (VC), and flowable composite (FC) which is recommended by some manufacturers. The objective of the study is to compare the depth of cure of (VC) and FC of porcelain veneer restorations and to determine the maximum thickness that will produce the greatest depth of cure using VC and FC.